2007
DOI: 10.1002/j.2050-0416.2007.tb00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Potential Beer-Spoilage Pediococcus inopinatus and Beer-Spoilage Lactobacillus backi Strains Carrying the horA and horC Gene Clusters

Abstract: Four beer-spoilage strains, LA20, LA21, LA22 and LA23, were isolated from brewery environments. Based on the 16S rRNA gene sequence, LA20 was identified as Pediococcus inopinatus and the remaining three were identified as Lactobacillus backi. The homologs of horA and horC, the hop resistance genes originally identified in L. brevis ABBC45, were detected simultaneously in LA22 and LA23, while only a horA homolog and a horC homolog were found in LA20 and LA21 respectively. The 5.6 kb DNA regions containing the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 20 publications
0
30
0
1
Order By: Relevance
“…paracollinoides and L. backi are strains of lactic acid bacteria (LAB) and have recently been proposed as new species 3,24,33 and their frequency in beer spoilage incidents is not well known. The genetic characterization indicates that L. paracollinoides and L. backi are closely related to L. collinoides and L. coryniformis, respectively and some of the strains belonging to L. paracollinoides and L. backi might have been misidentified as L. collinoides and L. coryniformis respectively in the past 3,43,44 .…”
Section: Soil Films Soil Films In the Brewing Industrymentioning
confidence: 99%
“…paracollinoides and L. backi are strains of lactic acid bacteria (LAB) and have recently been proposed as new species 3,24,33 and their frequency in beer spoilage incidents is not well known. The genetic characterization indicates that L. paracollinoides and L. backi are closely related to L. collinoides and L. coryniformis, respectively and some of the strains belonging to L. paracollinoides and L. backi might have been misidentified as L. collinoides and L. coryniformis respectively in the past 3,43,44 .…”
Section: Soil Films Soil Films In the Brewing Industrymentioning
confidence: 99%
“…L. paracollinoides, in particular, was shown to exhibit strong beer spoilage ability that is comparable with that of L. brevis and L. lindneri 110 . Although L. paracollinoides was once recognized as a rare beer spoilage species, it has been recently suggested that L. paracollinoides is more prevalent in brewing environments than initially anticipated 45 . The possibility that novel species become widespread poses a threat to the brewing industry that must maintain rigorous microbiological control systems in breweries.…”
Section: Taxonomy Of Sake and Beer Spoilage Labmentioning
confidence: 99%
“…lindneri, L. paracollinoides and P. damnosus are also frequently encountered species that exhibit strong beer spoilage ability 5,45 . With the exception for P. damnosus that is occasionally found in wineries, these species have been exclusively isolated from beer and related environments 5,45,100,104 , indicating L. lindneri, L. paracollinoides and P. damnosus are brewery-specific microorganisms.…”
Section: Association Of Beer Spoilage Lab With Their Habitatmentioning
confidence: 99%
“…Among them the most important spoilage organisms are, according to brewing literature, L. brevis, L. lindneri, L. paracollinoides and P. damnosus 2,30,32,34 . In addition, L. backi and P. inopinatus have been reported as potential beer spoilers 7,22,33 . A recently characterised strain, P. clausseni, has been shown to spoil beer 12 .…”
Section: Introductionmentioning
confidence: 99%
“…They exert bacteriostatic effects on most Gram-positive bacteria as they act as proton ionophores and dissipate the transmembrane pH gradient. Several LAB species, such as Lactobacillus spp., have been found to have acquired beer-spoilage ability due to hop resistance genes (horA and horC), and consideration must be given to the fact that altering the hop composition of beer can have a profound impact on the organoleptic and physico-chemical properties of the final product 6,21,22,33,35 .…”
Section: Introductionmentioning
confidence: 99%